Exploring Inquiry-Based Learning in Mathematics Education in the Canada-China Sister School Network: The Perspectives of Chinese Math Specialist Teachers - Chi, Chenkai; Xu, Shijing; Zhang, Li; Wei, Huarong (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
This narrative inquiry explores inquiry-based learning (IBL) in mathematics education through the Canada-China Sister School Network. It focuses on two Chinese mathematics specialist teachers at Chongqing RH Primary School, drawing on classroom observations, written reflections, and interviews collected from 2015 to 2022, in collaboration with Canadian generalist teachers at Windsor TL Public School. Guided by the framework of Reciprocal Learning as Collaborative Partnership and the three-dimensional narrative inquiry, the study examines how cross-cultural dialogue reshaped teachers’ understandings of IBL. Findings highlight differences between Canada’s generalist teaching model, which emphasizes student autonomy and interdisciplinary learning, and China’s specialist model, which focuses on content expertise and structured instruction. The study argues that reciprocal learning extends beyond comparative analysis to foster culturally responsive adaptations of IBL. By foregrounding teachers’ practical knowledge and lived experiences, this research demonstrates how sustained collaboration among teachers and researchers can reimagine mathematics education across cultural contexts, enriching both pedagogical theory and classroom practice.